Development of Child's Islamic Religious Aspects Through The Method of Training Education - Desi Ramandani Putri; Maskanatul Fiqiyah (International Tatho Academics, 2025)
This study aims to identify the application of habituation methods at SDIT Umar Bin Khathab Juwana in strengthening student religiosity. The research used a descriptive qualitative approach with data collection methods through interviews, observation, and documentation. Data were analyzed using the Miles & Huberman analysis technique, including data reduction, presentation, and conclusion drawing. The results showed that habituation methods, such as congregational prayer, dhikr, daily prayer, and memorization of the Qur'an, contribute to increasing student religiosity. Implementing this method requires synergy between teachers and parents to create a continuity of learning at school and home and overcome the main obstacle, which is maintaining the consistency of students' focus during habituation activities. In conclusion, the habituation method at SDIT Umar Bin Khathab Juwana supports the thoughts of Abdullah Nashih Ulwan, who emphasizes spiritual value-based education as the basis for moral formation.